2016
DOI: 10.1111/ipd.12262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the use of parental‐reported sleep bruxism in a polysomnographic study in children

Abstract: Although multiple-observation report achieved better agreement than single-observation report, our results failed supporting the validity of report strategies for the diagnosis of SB in children, as an equivalent of PSG/SB adult criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 30 publications
0
33
1
5
Order By: Relevance
“…The prevalence of SB in children is very variable, ranging from 3.5% to 46% . This variance may be attributed to fact that the diagnosis of SB in children is still challenging, once it is predominantly accessed through parental report.0 . Other validated methods such as physical examination and/or questionnaires are often used .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of SB in children is very variable, ranging from 3.5% to 46% . This variance may be attributed to fact that the diagnosis of SB in children is still challenging, once it is predominantly accessed through parental report.0 . Other validated methods such as physical examination and/or questionnaires are often used .…”
Section: Introductionmentioning
confidence: 99%
“…The sensibility and accuracy of parents' report of sleep bruxism are low, however, it shows excellent specificity when compared with polysomnographic findings 16 . The reliability of the questionnaire-based assessment of SB has been questioned 16 and its use has been of concern to several authors, both in studies involving adults 17,18 and children 3,16 . Despite its obvious limitations, the parental reports of SB remain important for epidemiological studies with large samples.…”
Section: Discussionmentioning
confidence: 99%
“…At least part of the wide prevalence range reported in the literature has been attributed to lack of distinction between wake-time and sleeprelated bruxism 7 . Restrepo et al 3 showed that when parentalreported sleep bruxism is based on multiple observations (5-day diary) there was a better agreement with polysomnography findings than the parental-report of a single observation (1-day diary).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruxism is as a repetitive jaw‐muscle activity characterized by clenching or grinding of the teeth, which can occur during sleep [sleep bruxism (SB)] or wakefulness [awake bruxism (AB)]. Current evidence suggests that SB may be viewed as a behavior, rather than a disorder, thus requiring a better definition of the clinical relevance of such phenomenon as a treatment‐demanding condition. To this aim, quantifying the masticatory muscle activity (MMA) associated with sleep bruxism yields fundamental information for understanding the role of SB as a risk factor for clinical consequences, such as temporomandibular disorders (TMD) and tooth wear, among others.…”
Section: Introductionmentioning
confidence: 99%